(untitled) - Stine, R. L.; Brown, Marc Tolon (New York, 2023)
"Why did the monster cross the road? To BITE someone on the other side! Turn scary to silly with this laugh-out-loud joke book."--Provided by publisher.
Keywords: Jokes; Fiction; Humorous stories; Fiction; Monsters; Juvenile fiction; Jokes; Juvenile fiction; Monsters; Picture books; Humorous fiction